2018
DOI: 10.1111/vru.12678
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial skills are better predictors than dexterity for basic ultrasonographic and fluoroscopic skills in veterinary students

Abstract: Radiological skills including ultrasonography and fluoroscopy, require a combination of manual dexterity and visuospatial skill to develop competency. The ability to detect veterinary students with an interest in radiology but who are deficient in these skills, may permit more individual adaptations to training programs, allowing for students training in radiology to achieve maximal potential. The objective of this cohort study was to investigate whether innate dexterity and visuospatial skill could be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…One study reported a significant relationship between the Dimensionless Squared Jerk, a validated motion metric that measures deliberate hand movements, and US expertise in obstetric US [ 58 ], while the other three papers did not find a significant relationship between psychomotor skills and US competence. [ 45 , 48 , 49 ] No correlation or determination coefficient was reported in the studies. Walker [ 49 ] found a regression coefficient of 0.00056 ( p = 0.580) for the Grooved Pegboard test performed by the non-dominant hand, and of − 0.0013 ( p = 0.329) when it was executed by the dominant hand, and time to complete an ultrasound guided cystocentesis task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a significant relationship between the Dimensionless Squared Jerk, a validated motion metric that measures deliberate hand movements, and US expertise in obstetric US [ 58 ], while the other three papers did not find a significant relationship between psychomotor skills and US competence. [ 45 , 48 , 49 ] No correlation or determination coefficient was reported in the studies. Walker [ 49 ] found a regression coefficient of 0.00056 ( p = 0.580) for the Grooved Pegboard test performed by the non-dominant hand, and of − 0.0013 ( p = 0.329) when it was executed by the dominant hand, and time to complete an ultrasound guided cystocentesis task.…”
Section: Resultsmentioning
confidence: 99%
“…[ 45 , 48 , 49 ] No correlation or determination coefficient was reported in the studies. Walker [ 49 ] found a regression coefficient of 0.00056 ( p = 0.580) for the Grooved Pegboard test performed by the non-dominant hand, and of − 0.0013 ( p = 0.329) when it was executed by the dominant hand, and time to complete an ultrasound guided cystocentesis task.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 34 ] Table 2 lists the tests related to the psychomotor domain used in medical sciences. [ 6 8 35 36 37 38 39 ] Attempts have been made, as far as possible, to note standard tests.…”
Section: Resultsmentioning
confidence: 99%
“…and the need to maintain anonymity due to IRB constraints, comparison of academic performance based on sex could not be performed.Heightened visuospatial skills can be particularly advantageous in diagnostic imaging due to the increased need to understand three-dimensional anatomy and perform procedures utilizing twodimensional imaging. A recent study evaluated both visuospatial aptitude and manual dexterity as predictors for baseline technical performance in simulated ultrasound and fluoroscopy tasks 28. The study found that innate visuospatial abilities as assessed by one of the three administered visuospatial tests correlated with faster ultrasound and fluoroscopic task performance, and that there were no significant differences between sexes.…”
mentioning
confidence: 99%